LEISURE TIME PHYSICAL ACTIVITY, LEISURE SATISFACTION AND SUBJECTIVE WELL-BEING: CAUSAL RELATIONSHIPS IN MIDLIFE. (11th November 2018) - Kekäläinen, T; Freund, A; Sipilä, S; Kokko, K
Abstract: Participation in leisure time physical activity (LTPA) in midlife is linked to both current well-being and many future benefits in older age. However, longitudinal analyses of the causal links between LTPA and well-being are lacking. Therefore, the aim of this study was to investigate longitudinal associations between LTPA and subjective well-being in middle adulthood. In addition, the role of leisure satisfaction in these relationships were investigated. The data gathered at ages 42 and 50 for the Finnish Jyväskylä Longitudinal Study of Personality and Social Development were used (present N=303). LTPA was asked as frequency of participation and leisure satisfaction as general satisfaction with one′s leisure time content. Subjective well-being was captured by mental well-being (including emotional, psychological and social well-being) and subjective health (including self-rated health and psychosomatic symptoms). Participation in LTPA did not predict mental well-being or subjective health. Instead, mental well-being predicted LTPA. Both mental well-being and subjective health predicted leisure satisfaction. Of the participants, 57% were physically active and 12% inactive at both measurement points, 21% moved from inactive to active and 10% from active to inactive. Increase in LTPA was related to increase in leisure satisfaction. The results suggest that longitudinally subjective well-being is more likely to be causally linked to leisure satisfaction and LTPA than vice versa. Additionally, changes in LTPA and leisure satisfaction during midlife are related to each other. It would be important to encourage middle-aged adults to find the time to participate in LTPA, even if their leisure time may be limited.